Awareness about human papilloma virus and its vaccine among young women - Seshaiyengar, Chaluvaraj Talkad; Chikkegowda, Lokesh Kabbalu; Madaiah, Madhusudan; Munipapanna, Santhosh; Sonnappa, Suresha Doddasabbenahalli (International Journal Of Community Medicine And Public Health, 2017)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: In India, cancer cervix is the leading type of cancer. It is estimated that nearly 100,000 new cases of cervical cancer occurring annually contributing significantly for death of Indian women and it is on the progressive increase. HPV has been incriminated as important cause of cancer cervix. Thus, the study aimed at assessing the extent of awareness and attitude towards Human papilloma virus, HPV vaccine and cervical cancer among young Women in Medical and Nursing College. Methods: Cross sectional study done on 1st year female medical and nursing students (18-21years of age) for the period of One month. Pre-tested, semi structured, self-administered questionnaire was used for the collection of data regarding HPV and its vaccine. Statistical analysis was done by simple percentages and proportions. Frequency and percentages were evaluated for categorical variables. Fisher’s exact test is used to identify the association between categorical variables. Results: In this study 83% of the study Subjects were aware of the disease cancer cervix and 79% of the study Subjects were aware of the Human Papilloma Virus and the association between the causation of cancer cervix by HPV virus is known only by 46%. Awareness about HPV vaccination was 59%, out of which 19% were vaccinated; 41% were neither aware of HPV vaccine nor taken vaccination. However, study showed a strong association between awareness about HPV vaccination and vaccinated, which is statistically significant with Fisher’s Exact p value <0.05. Conclusions: There is need to augment the Information, Education and Communication (IEC) activities to create awareness at all levels in the community in general and among young Women in particular to avert future misery of Women folk who suffer silently. Delhi, first state to launch HPV vaccine as public health programme in schools from March 1st 2016. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>